Summer hours = L' heure d'été - Assayas, Olivier 1955-; Gautier, Éric 1961-; Binoche, Juliette 1964-; Berling, Charles 1958-; Renier, Jérémie 1981- (The Criterion collection, 2010)
The divergent paths of three adult siblings collide when their mother, heiress to an exceptional 19th century art collection, dies suddenly.